Enhancing Hydrogen Evolution Activity of Au(111) in Alkaline Media through Molecular Engineering of a 2D Polymer. (18th March 2020) - Alexa, Patrick; Lombardi, Juan Manuel; Abufager, Paula; Busnengo, Heriberto Fabio; Grumelli, Doris; Vyas, Vijay S.; Haase, Frederik; Lotsch, Bettina V.; Gutzler, Rico; Kern, Klaus
Abstract: The electrochemical splitting of water holds promise for the storage of energy produced intermittently by renewable energy sources. The evolution of hydrogen currently relies on the use of platinum as a catalyst—which is scarce and expensive—and ongoing research is focused towards finding cheaper alternatives. In this context, 2D polymers grown as single layers on surfaces have emerged as porous materials with tunable chemical and electronic structures that can be used for improving the catalytic activity of metal surfaces. Here, we use designed organic molecules to fabricate covalent 2D architectures by an Ullmann‐type coupling reaction on Au(111). The polymer‐patterned gold electrode exhibits a hydrogen evolution reaction activity up to three times higher than that of bare gold. Through rational design of the polymer on the molecular level we engineered hydrogen evolution activity by an approach that can be easily extended to other electrocatalytic reactions. Abstract : Den Vulkan hoch : Die elektrochemische Produktion von Wasserstoff kann durch das Zusammenwirken eines 2D‐Polymers und einer Goldelektrode verstärkt werden. Modifikation der molekularen Struktur des Polymers verändert die Adsorptionsenergien der Reaktanten, Intermediate und Produkte, und hilft somit, Gold Richtung Spitze des Vulkan‐Plots zu bewegen.